Variable Exponent Herz-Morrey-Hardy Spaces Characterized by Wavelets and Its Application (Analysis in Theory and Applications, 2023)
In this paper, using the atomic decomposition of the Herz-Morrey-Hardyspaces with variable exponent, the wavelet characterization by means of a local versionof the discrete tent spaces with variable exponent is established. As an application, theboundedness of the fractional integral operators from variable exponent Herz-Morrey-Hardy spaces into variable exponent Herz-Morrey spaces is obtained.
Keywords: Wavelet; variable exponent; characterization; Herz-Morrey-Hardy space.